A digital transformation approach to scaffold tourism crowding management: Pre-factum, on-factum, and post-factum - Brito e Abreu, F.; Marinheiro, R. N.; Boavida-Portugal, I.; Lopes, A.; Santos, T.; Sampaio de Almeida, D.; Simões, R. (Proceedings - 2024 Joint International Conference on Digital Arts, Media and Technology with ECTI Northern Section Conference on Electrical, Electronics, Computer and Telecommunications Engineering, ECTI DAMT and NCON 2024, 2024)
Tourism would probably not be economically sustainable without some localized crowding phenomena. Whatever the carrying capacity of the points of interest, their tourism managers should plan, monitor, and analyze visitors' crowding data to either prevent or mitigate the well-known effects of tourism overcrowding, such as degrading the tourists' experience, impacting negatively the environment and the local population, be it humans or wildlife. The proposed digital transformation approach comprises three smart tourism tools (STTs) to scaffold crowding management issues, especially those related to overcrowding, i.e. when the carrying capacity of points of interest is exceeded. We report on the development and validation experiments of these STTs in the scope of the European Union RESETTING project. The pre-factum STT aims at supporting simulation-based participatory discussions among tourism destination stakeholders. Proactive planning based on simulated scenarios allows the identification of potential tourism overcrowding situations and experimenting with possible mitigation actions. The on-factum STT enables local monitoring of tourism crowding, by using several Wi-Fi activity sensors. The ability to obtain near real-time data, allows short-term decision-making, such as reinforcing or freeing up human and technical resources assigned to managing tourist crowding on the ground. The post-factum STT is a geo-temporal 3D visualization platform to explore historical crowding data, visualize patterns, and understand and forecast trends. The main objectives of this STT are fostering cumulative learning from experience and forecasting the recurrence of troublesome crowding situations, allowing us to plan for mitigation actions.